Sengoku youko. 3 - Mizukami, Satoshi (Tokyopop Inc., 2023)
The world is divided into two factions: humans and monsters called katawara. Despite being a katawara, Tama loves humans and vows to protect them from evil, even if it means fighting her own kind. Her stepbrother Jinka, however, hates humans, despite mostly being one. The siblings are joined by a swordsman-in-training named Shinsuke and a human-katawara experiment named Shakugan. After angering the Dangaishuu, a group of spiritual warriors experimenting on humans to turn them into katawara, Jinka is being pursued by their four beast leaders. Will he be able to stop all four powerful leaders and keep his new companions safe?